2020
DOI: 10.1016/j.ajps.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Biointerface engineering nanoplatforms for cancer-targeted drug delivery

Abstract: Over the past decade, nanoparticle-based therapeutic modalities have become promising strategies in cancer therapy. Selective delivery of anticancer drugs to the lesion sites is critical for elimination of the tumor and an improved prognosis. Innovative design and advanced biointerface engineering have promoted the development of various nanocarriers for optimized drug delivery. Keeping in mind the biological framework of the tumor microenvironment, biomembrane-camouflaged nanoplatforms have been a research fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 129 publications
(187 reference statements)
0
47
0
Order By: Relevance
“…Conventional dose-delivery of therapeutic agents require frequent administration to provide the proper therapeutic dosage, above the minimum therapeutic level and below the minimum toxic level [30]. However, bioavailability of the drugs and dose-dependent side effects are some of many limitations of the traditional drug delivery methods, like oral or intravenous injections [30][31][32][33][34][35]. To overcome these limitations, controlled drug delivery systems are being explored in different applications, specially cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional dose-delivery of therapeutic agents require frequent administration to provide the proper therapeutic dosage, above the minimum therapeutic level and below the minimum toxic level [30]. However, bioavailability of the drugs and dose-dependent side effects are some of many limitations of the traditional drug delivery methods, like oral or intravenous injections [30][31][32][33][34][35]. To overcome these limitations, controlled drug delivery systems are being explored in different applications, specially cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Thiolated heparin-pheophorbide A (PhA) conjugated magnetic iron oxide/gold hybrid nanoparticle Therapeutics Phototoxicity and strong fluorescence signals from the NPs result in A549 cells deaths under light irradiation. [23] 3.…”
Section: Hypericin-bearing Magnetic Iron Oxide Nanoparticles Therapeumentioning
confidence: 99%
“…Active Targeting: The basis of active targeting strategy includes the interaction of ligand-stocked drug carrier with surface-exposed receptors on the target cells, which helps in their assemblage in a tumor, and also assists their intracellular accretion through receptor-mediated endocytosis [ 21 ]. Tumor cells are usually overexpressed with one or more types of specific receptors which may act as a target site for the active targeting through ligand-functionalized nanoparticles [ 22 , 23 ]. Thus, the tumor and endothelial cells are recognized as cellular targets for active targeting approach.…”
Section: Cancer Nanotechnology: Contemporary Research In Diagnosismentioning
confidence: 99%
“…New approaches for cancer immunotherapy are needed to promote the therapeutic potential of therapeutic payloads through a safer and more controlled manner. A large and growing body of studies have demonstrated the synergistic effects of biomaterials combined with cancer immunotherapy direct the path to address these limitations (Guo et al, 2020;Sang et al, 2019;Zhang et al, 2020). Lately, a variety of biomaterials, such as nanoparticles, implantable biomaterial scaffolds and injectable biomaterial scaffolds, have been introduced to promote immune response and improve the anti-tumor effect (Feng et al, 2020;Li et al, 2019;Wang et al, 2020;Xie et al, 2018).…”
Section: Introductionmentioning
confidence: 99%